Effects of social confinement during the first wave of COVID-19 in Mexico City - Segura-García, Stephany; Barrera-Ramírez, Ameyalli; Gutiérrez-Esparza, Guadalupe O.; Groves-Miralrio, Elizabeth; Martínez-García, Mireya; Hernández-Lemus, Enrique (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic led to global social confinement that had a significant impact on people's lives. This includes changes such as increased loneliness and isolation, changes in sleep patterns and social habits, increased substance use and domestic violence, and decreased physical activities. In some cases, it has increased mental health problems, such as anxiety, depression, and post-traumatic stress disorder. Objective The objective of this study is to analyze the living conditions that arose during social confinement in the first wave of COVID-19 within a group of volunteers in Mexico City. Methods This is a descriptive and cross-sectional analysis of the experiences of volunteers during social confinement from 20 March 2020 to 20 December 2020. The study analyzes the impact of confinement on family life, work, mental health, physical activity, social life, and domestic violence. A maximum likelihood generalized linear model is used to determine the association between domestic violence and demographic and health-related factors. Results The findings indicate that social confinement had a significant impact on the participants, resulting in difficulties within families and vulnerable conditions for individuals. Gender and social level differences were observed in work and mental health. Physical activity and social life were also modified. We found that suffering from domestic violence was significantly associated with being unmarried (OR = 1.4454, p-value = 0.0479), lack of self-care in feeding habits (OR = 2.3159, p-value = 0.0084), and most notably, having suffered from a symptomatic COVID-19 infection (OR = 4.0099, p-value = 0.0009). Despite public policy to support vulnerable populations during confinement, only a small proportion of the studied population reported benefiting from it, suggesting areas for improvement in policy. Conclusion The findings of this study suggest that social confinement during the COVID-19 pandemic had a significant impact on the living conditions of people in Mexico City. Modified circumstances on families and individuals, included increased domestic violence. The results can inform policy decisions to improve the living conditions of vulnerable populations during times of social confinement.